2022
DOI: 10.7759/cureus.21851
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbilirubinemia as a Possible Predictor of Appendiceal Perforation in Acute Appendicitis: A Prospective Study

Abstract: Introduction: Acute appendicitis, a common abdominal surgical emergency, can mostly be diagnosed clinically by assessing the symptoms and physical findings but confirmation of the diagnosis solely depends upon the histopathological study of the resected appendix specimen, being supplemented by a few laboratory tests and ultrasonography (USG). In spite of all these available investigations, the diagnosis of acute appendicitis, because of its nebulous presentation and the variability of signs, remains a Herculea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Similarly, for differentiating perforated appendicitis from non-perforated appendicitis, serum bilirubin levels showed sensitivity, specificity, PPV, and NPV of 70.59%, 80.97%, 43.37%, and 93.02%, respectively. Our findings are consistent with those of the study conducted by Kar et al [18], except for the specificity for perforated appendicitis, which was higher in the present study.…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, for differentiating perforated appendicitis from non-perforated appendicitis, serum bilirubin levels showed sensitivity, specificity, PPV, and NPV of 70.59%, 80.97%, 43.37%, and 93.02%, respectively. Our findings are consistent with those of the study conducted by Kar et al [18], except for the specificity for perforated appendicitis, which was higher in the present study.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, from table 5 it is seen that the sensitivity, positive predictive value, and negative predictive value of total serum bilirubin in suspected acute appendicitis was 74.59%, 71.06%, and 14.44%, respectively, which matches the findings of a similar study conducted by Kar et al, 13 in February 2022, in which their figures were 57.02%, 97.01%, and 15.52%, respectively. In another study by Chaudhary et al, 14 hyperbilirubinemia was of mixed type (conjugated and unconjugated elevation), but it was total serum bilirubin that was predominantly raised.…”
Section: Discussionsupporting
confidence: 90%
“…In 90% patients of perforated appendicitis there's increased bilirubin levels as reported byGavriilidis et al 5 In another study, hyperbilirubinemia was observed in 48% patients of perforated appendicitis. 7 In the research analysiscarried out by Chaudhary et al, hyperbilirubinemia was noticed in the cases of acute suppurative appendicitis, and was much more elevated in cases of perforated as well as gangrenous appendicitis 12,13 .…”
Section: Discussionmentioning
confidence: 96%
“…In recent past, studies have purposed that value of serum bilirubin could be a helpful tool in the diagnosis of acute appendicitis 11 . Aspecific relationship might exist between bacteria and serum bilirubin that's why bilirubin levels are raised in appendicitis and other inflammatory conditions of abdomen including bacterial peritonitis and intestinal perforation 12 .…”
Section: Discussionmentioning
confidence: 99%